Exploring the Role of Brand Equity on Customer Satisfaction and Brand Loyalty: A Case Study of Browcyl's Signature Makassar Snacks - Hasbiah, Sitti (PT. Maju Malaqbi Makkarana, 2023)
This study aims to explore the relationship between consumer-based brand equity and brand loyalty, with an emphasis on the mediating role of customer satisfaction in the specific context of the cake shop segment within the restaurant industry. Employing Structural Equation Modeling (SEM) through LISREL, this research analyzes data collected from customers of Browcyl’s cake shops in Makassar. The model focuses on examining the impact of five dimensions of consumer-based brand equity on customer satisfaction and, subsequently, on brand loyalty. The results indicate that three out of the five dimensions of consumer-based brand equity significantly and positively influence customer satisfaction. In turn, customer satisfaction has a strong, positive impact on brand loyalty. This highlights the pivotal role of certain brand equity elements in enhancing customer satisfaction, which is a key driver of brand loyalty in the cake shop sector. The study offers valuable insights for practitioners in the restaurant industry, particularly in the cake shop sector. It suggests that focusing on specific aspects of brand equity can significantly improve customer satisfaction, leading to increased brand loyalty. This provides a strategic direction for cake shop owners and marketers to strengthen their brand equity in ways that resonate with their customers.